Andrushchenko M.І., Osіpov M.Y., Kulikovsky R.A., Kapustіan О.YЕ., Magda Е.S. Materials, tech-nology and special equipment for strengthening and restoration of dies for pressing the hollow cylindrical refractory. Part 2. Features of hardening and restorat - Андрущенко, М.И.; Осипов, М.Ю.; Куликовский, Р.А.; Капустян, А.Е.; Магда, Е.С. (Problems of Tribology, 2017)
Based on preliminary laboratory test results of deposited metal on abrasion resistance presented by the first part of this study, as well as the chosen manufacturing experience seven types of electrode materials for arc welding working edges of dies used in the extrusion of hollow cylindrical refractories. weld metal structure within a selected group changed from ferrite to hypereutectic with martensite-austenite base and 40-50 % of eutectic and primary carbides.Optimal modes surfacing outer and inner edges of the stamps and offered special equipment (water-cooled conditioners), providing the necessary cooling rate and given a uniform structure of the deposited metal.Carried out production tests surfaced dies in the manufacture of alumino-silicate refractories. It is found that a relatively high potential hypereutectic composition of the metal is virtually impossible to realize due to spallation fragments deposited layer. The most optimal combination of the reliability and durability of the weld metal is achieved with the type of 65Х11Н3 austenite-martensite structure, due to the partial conversion of the metastable austenite to martensite.Key words: stamp, structure, abrasion, wear conditions, the weld metal cooling rate, ferrite, martensite, austenite, wear resistance, microhardness.